GAMBARAN BIAYA LANGSUNG PADA PASIEN KRISIS HIPERTENSI RAWAT INAP DI RSUP DR. SARDJITO, YOGYAKARTA: OVERVIEW OF DIRECT COSTS IN INPATIENTS WITH HYPERTENSIVE CRISIS AT RSUP DR. SARDJITO, YOGYAKARTA - Dwi Ismayati; Dwi Endarti; Fita Rahmawati (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Hypertensive crisis imposes a substantial economic burden on healthcare systems. In Indonesia, rising service costs necessitate health economic evaluations to optimize hospital management. This study aims to analyze the direct costs of hypertensive crisis patients at RSUP Dr. Sardjito, Yogyakarta. A descriptive observational study with a retrospective cohort design was conducted on hypertensive crisis patients from January 2018 to July 2022. A total of 37 subjects were selected using a purposive sampling technique. Patients were divided into Calcium Channel Blocker (CCB) therapy groups (n=31) and non-CCB therapy groups (n=6). Cost components analyzed included medication costs, accommodation, inpatient / ER care, and radiodiagnostics. Statistical analysis used an independent sample t-test. The average total direct cost was IDR 3,282,080. The largest cost component for all subjects was inpatient/ER care costs of IDR 1,154,261 (35.17%). The average total cost in the CCB group was IDR 3,068,395, while in the non-CCB group it was IDR 4,386,119. Despite the cost difference, statistical tests showed no significant difference between the two therapy groups (p = 0.127). There was no significant difference in costs between the use of CCB and non-CCB therapy. These results can be used as a reference in budget planning and management of hypertensive crisis therapy in hospitals. Keywords: CCB, Direct costs, Hypertensive crisis, Pharmacoeconomics